(untitled) (Oratio Directa, 2025)
Digital citizenship provides broad opportunities for public participation without requiring physical mobility. This qualitative descriptive study examines digital citizens' use of online petitions as instruments of social control on Change.org. Primary data comprise textual observations of petition narratives, reasons for signing, and comment fields; secondary data include literature, news reports, and policy documents. The analysis focuses on the #JusticeForAudrey petition and petitions opposing a 12 percent value-added-tax policy. The findings show that online petitions can amplify agenda-setting, public attention, and policy criticism, but signatures alone do not necessarily produce policy change. Their influence depends on complementary advocacy through media, campaigns, and civil-society organizations. The cases also demonstrate that high accessibility and rapid participation can precede factual verification and generate unaccountable social judgment. Digital citizenship can therefore support social control only when participation is accompanied by digital ethics, verification, and accountable advocacy.